Croyances religieuses en milieu urbain: Ouagadougou - Deniel, R. (Social compass, 1969)
The author gives the provisional results of a survey carried out in Ouagadougou, the capital of Upper Volta. Using the degree of religious culture as the basic variable, it can be seen that the attitude of the young people differs considerably from that of the adults. The adults appear more concerned about death and a future life, while the characteristic note of the young people is that of a certain rebellion against religious precepts of Christianity and Mohammedanism. The adults' socio-economic values are centred on children and security; the young people, on the other hand, seem more interested in their profession and their personal development.There is little connection between these notions and religion as a whole. However, religion gives the adults a certain feeling of security. For the young people it often tends to be a moral frame or a help for some immediate problem (examinations), which very often leads them to a radical questioning of all belief.The role of religion in development is seen, above all, as a contribution to the fields of literacy and health, as well as being a means of social cohesion among its adherents. Because the majority of the 'elite' are Christians, one must not overlook the unfavorable situation of the ani mists and the Moslems. The author concludes with a warning against a possible oversimplification with regard to the role of religion in devel opment.